Torque ripples improvement of direct torque controlled five-phase induction motor drive using backstepping control - Hamdi Echeikh; Ramzi Trabelsi; Hichem Kesraoui; Atif Iqbal; Mohamed Faouzi Mimouni (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The paper proposes Direct Torque Control (DTC) of a five-phase induction motor drive with reduced torque ripple. The method presented here is the DTC Backstepping based on the classic DTC working with a constant switching frequency of the inverter. Another remarkable aspect is the complexity of the method proposed, both in the control unit of the inverter and in the number of correctors necessary for the control of the torque. The selection table and hysteresis have been eliminated. This method significantly improves the torque and flux oscillations and improves the dynamics of the drive by making it less sensitive to load torque disturbances. The proposed method is developed and designed using Matlab/SIMULINK to show the eectiveness and performances of the DTC-Backstepping.